Application of advanced anodes in microbial fuel cells for power generation: A review. (June 2020) - Cai, Teng; Meng, Lijun; Chen, Gang; Xi, Yu; Jiang, Nan; Song, Jialing; Zheng, Shengyang; Liu, Yanbiao; Zhen, Guangyin; Huang, Manhong
Abstract: Microbial fuel cells (MFCs) the most extensively described bioelectrochemical systems (BES), have been made remarkable progress in the past few decades. Although the energy and environment benefits of MFCs have been recognized in bioconversion process, there are still several challenges for practical applications on large-scale, particularly for relatively low power output by high ohmic resistance and long period of start-up time. Anodes serving as an attachment carrier of microorganisms plays a vital role on bioelectricity production and extracellular electron transfer (EET) between the electroactive bacteria (EAB) and solid electrode surface in MFCs. Therefore, there has been a surge of interest in developing advanced anodes to enhance electrode electrical properties of MFCs. In this review, different properties of advanced materials for decorating anode have been comprehensively elucidated regarding to the principle of well-designed electrode, power output and electrochemical properties. In particular, the mechanism of these materials to enhance bioelectricity generation and the synergistic action between the EAB and solid electrode were clarified in detail. Furthermore, development of next generation anode materials and the potential modification methods were also prospected. Graphical abstract: Can the power generation and wastewater treatment like "Tai Chi" is complementary. Image 1 Highlights: Elucidating difference nature advanced materials for anode decoration in MFCs. Analyzing the reason of anode electrode to enhance bioelectricity generation. Investigation the synergistic effects between microbes and solid electrode. Summarizing fabrication technique for high performance anode electrodes. Proposing possible modification methods for next-generation anode electrodes.